Adolescence between biology and culture a perspective on the crisis of symbolization - Carta, Stefano; Cataudella, Stefania (Frontiers in Psychology, 2022)
One way to conceptualize human life is to describe it as a process through which the biological body is progressively transformed into a psychological one through its mentalization and symbolization. This process occurs through the relational field, which begins with caregiver-infant proto-conversations and develops through adolescence into the ongoing complex interpersonal relational network we call society and culture. The essence and the problems of the adolescents are intricately tied to the social and cultural contexts in which they experience life (Israel et al., 2021). Therefore, adolescence cannot be understood if all the levels that it expresses (biological, psychological cultural/social) are not taken into consideration. We identify three psycho-historical phases through which adolescence has changed in the past century: 1) Oedipal; 2) Narcissistic; 3) Post-narcissistc. In this last phase due to the psychological and historical failure of the narcissistic ideals, the Ideal is mingling with the Real in a wholly new way. This process has overturned Erikson’s paradigm: Identity, opposed and defined by a dichotomic Otherness, must be transformed into a fluid integration of similarities and differences negotiated and developed through empirical interpersonal intersubjective experiences. This, in our perspective, is a possible key to understand the rapid change of the nature of consciousness, selfhood and gendering in today’s western world, together with some important psychopathological disorders which describe the new creative challenges of today’s adolescents.